Uwarunkowania transformacji polityki energetycznej Francji. Między ekologiczną modernizacją a ekonomiczną kalkulacją - Młynarski, Tomasz (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2015)
Dotychczasowa polityka energetyczna Francji była skoncentrowana na efektywności energetycznej i standardach bezpieczeństwa energetyki jądrowej, w mniejszym stopniu zaś na rozwoju nowych zielonych źródeł energii. W ramach nowej polityki transformacji energetycznej, zaproponowano wiele inicjatyw w zakresie rozwoju energetyki odnawialnej, zbliżając się do niemieckiej wizji transformacji energetycznej. Francuskie elity polityczne uznały, że rozwój OZE ma znaczenie strategiczne nie tylko dla zaspokojenia potrzeb energetycznych kraju, ale także - w obliczu zaostrzania reżimu ograniczenia emisji gazów cieplarnianych (GHG) - jest szansą na zbudowanie przewagi konkurencyjnej innowacyjnej gospodarki i stworzenie wielu nowych miejsc pracy. W efekcie, ekologiczna modernizacja gospodarki przez nieemisyjne innowacje technologiczne ma zapewnić postęp w osiągnięciu celów środowiskowych z jednoczesnym postępem industrialnym i wzrostem gospodarczym (sustainable development).

The project of ecological modernisation - widely integrating all aspects of economic transformation - is one of the flagship ideas of incumbent French President François Hollande and the French Socialists. The current energy policy of France, one of the largest global and European energy consumers, is focused on energy efficiency and technological safety standards in the nuclear industry, and to a lesser extent on the development of new green energy technologies. Approaching the German vision of energy transformation, the new French policy has proposed several initiatives for the development of renewable sources. France realised that the development of renewable energy is of strategic importance, not only to meet the energy needs of the country, but also - in the face of the stricter regime of GHG emissions reductions - to provide a competitive advantage for an innovative economy and an opportunity to create many new jobs. Ecological modernisation of the economy is supposed to ensure progress in achieving environmental goals, together with the progress of industrialisation and economic growth (sustainable development).
The determinants of the transformation of energy policy in France. Between ecological modernisation and economic calculations
Keywords: transformacja; polityka energetyczna; Francja; ekonomia; transformation; energy policy; France; economy